Goñerriko hizkera (I) - Camino, Iñaki (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1999)
This paper gives a general overview of the extinct Basque variety from the Goñi Valley, near Pamplona. Amongst Basque varieties, this is a geolinguistically central one, though quite western within Navarrese Basque. Existing Goñi Valley texts from the XVIII and XIX centuries are only relatively diatopic. Goñi Basque is compared here with varieties in the Pamplona area and dialects from the other side of the Andia Mountains in Sakana. The aim is to discover possible geolinguistic connections between Goñi Valley variety and neighbouring ones and to determine its distinctive characteristics. The present study follows along the lines of previous dialectology work by O. Ibarra (1995), K. Zuazo (1994) and P. Salaberri (1998).